Fluorescent Metallacycle‐Cored Amphiphilic Nanoparticles Formed by β‐Cyclodextrin‐Based Host–Guest Interactions towards Cancer Theranostics. Issue 57 (11th September 2020) - Ma, Lingzhi; Yang, Tianfeng; Li, Shuya; Zhang, Zeyuan; Lu, Shuai; Jeyakkumar, Ponmani; Song, Zhongxiao; Li, Xiaopeng; Yu, Guocan; Chu, Dake; Liu, Hang; Zhang, Yanmin; et al.
Abstract: Theranostic agents, taking the advantages of both imaging and therapeutic functions, are anticipated to be key components in the development of personalized medicine in which the therapeutic response can be real‐time monitored. Herein, three metallacycles with pendent adamantane groups are prepared by coordination‐driven self‐assembly of Pt II ligands with anticancer activities and tetraphenylethylene derivatives with emission. β‐Cyclodextrin, which shows good host–guest interactions with adamantane moieties, was added to form amphiphilic supramolecular nanoparticles with the aim to enhance the aqueous solubilities and bioactivities of these metallacycles. Moreover, when rhodamine‐modified β‐cyclodextrin was used as the carrier, the release of the metallacycles from the nanoparticles could be monitored in situ through the fluorescence changes owing to the efficient fluorescence resonance energy transfer from the metallacycles to rhodamine‐modified β‐cyclodextrin. In vitro and in vivo studies showed that these nanoparticles not only served as cell imaging contrast agents but also displayed improved anticancer activities, allowing them to serve as potential candidates for cancer theranostics. This study provides a simple and efficient method to prepare theranostic agents by hierarchical supramolecular self‐assembly, which will pave the way for image‐guided cancer therapy, targeted cancer therapy, and related biomedical fields. Abstract : Cancer theranostics : Based on hierarchical self‐assembly, amphiphilic supramolecular nanoparticles were prepared by the addition of fluorescent metallacycles into the aqueous β‐cyclodextrin solution. In vitro and in vivo studies showed that these nanoparticles served as contrast agents for cell imaging and exhibited improved bioactivities and anticancer activities, suggesting that they can be used for cancer theranostics.